2003
DOI: 10.1097/00001665-200303000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on Naturally Absorbable Osteofixation Devices

Abstract: The practice of using implants is growing day by day, and more foreign materials are being inserted for various indications. The field of implantology thus deserves intensive research and careful evaluation of results. Solutions to overcome current problems and risks are necessary. It has taken a long time to arrive at where we are now. Bioabsorbable devices were explored in the 1960s for surgical bone fixation. Failures were followed by changes in ways of thinking and innovations. Improvements in the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 113 publications
0
34
0
2
Order By: Relevance
“…Polylactide (PLA) and polyglycolide (PGA) acid are the most commonly used biodegradable (co)polymers in surgery especially in osteosynthesis [1][2][3][4], and in general are considered safe for clinical use [5], although unexpected phenomena such as long degradation periods are not uncommon [6,7]. The aim for the use of these degradable polymers is the prevention of repeated surgery for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Polylactide (PLA) and polyglycolide (PGA) acid are the most commonly used biodegradable (co)polymers in surgery especially in osteosynthesis [1][2][3][4], and in general are considered safe for clinical use [5], although unexpected phenomena such as long degradation periods are not uncommon [6,7]. The aim for the use of these degradable polymers is the prevention of repeated surgery for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…8,12,13 Furthermore, the foreign body has disappeared and the risk for infection is thereby reduced. 2 In this study, degradation of magnesium alloy implants and new bone formation was demonstrated in a living organism. The two study groups revealed different degradation stages in correlation with varying extents of ossification.…”
Section: Discussionmentioning
confidence: 92%
“…To avoid these problems and the need for a follow-up operation for implant removal in orthopedics, bioabsorbable materials which degrade after serving their purpose were investigated. 2,3 In orthopaedics, especially polymers like polyglycolic acid and polylactic acid were used as plates or screws, but showed adverse effects like local tissue reactions. 4 The same polymers were examined as cardiovascular devices such as coronary stents, but revealed excessive neointima proliferation with complete occlusion of vessels and inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Use of biodegradable drug delivery systems evades the need for additional surgery required by nonresorbable systems, such as polymethylmethacrylate (PMMA) beads. 6,10,11 Calcium sulfate, a biocompatible, biodegradable material, is an interesting candidate for local delivery in cases of trauma because extensive bone damage is common. Calcium sulfate improves bone healing and repair, even when loaded with an antibiotic.…”
mentioning
confidence: 99%